Human Lung Cancer Cell Line A-549 ATCC Is Differentially Affected by Supranutritional Organic and Inorganic Selenium - Lérida Liss Flores Villavicencio; Gustavo Cruz-Jiménez; Gloria Barbosa-Sabanero; Carlos Kornhauser-Araujo; M. Eugenia Mendoza-Garrido; Guadalupe de la Rosa; Myrna Sabanero-López (Bioinorganic Chemistry and Applications)
The effects of organic and inorganic forms of selenium (Se) on human cells have been extensively studied for nutritional concentrations; however, to date, little is known about the potential toxicity at supranutritional levels. In the present study we determined the effects of sodium selenite (SSe) and selenomethionine (SeMet) on cell growth and intracellular structures in lung cancer cells exposed at Se concentrations between 0 and 3 mM. Our results showed that SSe affected cell growth more rapidly than SeMet (24 h and 48 h, resp.). After 24 h of cells exposure to 0.5, 1.5, and 3 mM SSe, cell growth was reduced by 10, 50, and 60%, as compared to controls. After 48 h, nuclear fragmentation was evident in cells exposed to SSe, suggesting an induction to cell death. In contrast, SeMet did not affect cell proliferation, and the cells were phenotypically similar to controls. Microtubules and microfilaments structures were also affected by both Se compounds, again SSe being more toxic than SeMet. To our knowledge, this is the first report on the differential effects of organic and inorganic Se in supranutritional levels in lung cancer cells.